The effects of booster vaccination of hepatitis B vaccine on children 5–15 years after primary immunization: A 5-year follow-up study. Issue 5 (4th May 2018) - Wu, Zikang; Yao, Jun; Bao, Hongdan; Chen, Yongdi; Lu, Shunshun; Li, Jing; Yang, Linna; Jiang, Zhenggang; Ren, Jingjing; Xu, Kai-jin; Ruan, Bing; Yang, Shi-gui; et al.
ABSTRACT: The aim of this study was to evaluate changes in hepatitis B surface antibody titers (anti-HBs) after booster vaccinations in children aged 5–15 y and to provide suitable immunization strategies. A total of 2208 children were initially enrolled in screening, and 559 children were finally included. The participants were divided into 2 groups according to their pre-booster anti-HBs levels: Group I, <10 mIU/ml and Group II, ≥10 mIU/ml. Group I was administered 3 doses of booster hepatitis B vaccine (0-1-6 months, 10 μg), and Group II was administered 1 dose of booster hepatitis B vaccine (10 μg). The antibody titer changes were examined at 4 time points: 1 month after dose 1 and dose 3, and 1 year and 5 years after dose 3. The protective seroconversion rates at those points were 95.65%, 99.67%, 97.59% and 91.05% ( p < 0.001), respectively, in Group I, and 100.00%, 99.87%, 99.66% and 98.21% ( χ 2 = 6.04, p = 0.11), respectively, in Group II. The GMT in subjects aged 5–9 y were higher than that in subjects aged 10–15 y in both Group I and Group II at 1 month after dose 1, but no difference was observed at the other three time points. This study demonstrates that booster vaccination has a good medium-term effect. A booster dose for subjects with protective antibodies is not necessary but effective, and 3 doses of hepatitis B vaccination are recommended for those who have lost immunological memory. Receiving booster immunization at the age of 10-15 years may be more appropriate for individuals living in HBV high epidemic areas